Association of plasma lipids fatty acid composition with metabolic profile of Czech adolescents - Hlavaty, P; Tvrzicka, E; Stankova, B; Zamrazilova, H; Sedlackova, B; Dusatkova, L; Hainer, V; Kunesova, M (Physiological research, 2015)
Obesity in childhood increases the risk of obesity in adulthood and is predictive for the development of metabolic disorders. The fatty acid composition is associated with obesity and obesity-associated disorders. We investigated the relationship between serum fatty acids composition, adiposity, lipids profile, parameters of glucose metabolism and leptin. The study subjects were 380 adolescents aged 15.0-17.9 years. The study's variables included anthropometric measurements, levels of serum lipids and hormonal parameters. Individual fatty acids were determined in plasma by gas-liquid chromatography. Palmitoleic acid (16:1n-7, PA) significantly positively correlated with percentage of body fat. Saturated fatty acids in phospholipids (PL) positively correlated with BMI and percentage of body fat. PA content in all lipids classes positively correlated with total cholesterol (TC), HDL cholesterol, triglycerides (TG) levels. Stearoyl-CoA desaturase (SCD) activity positively correlated with percentage of body fat and positive correlations of SCD and PA level with leptin were found. Plasma PA content and SCD are associated with adiposity and leptin in obese adolescents. No significant correlation between PA level and insulin resistance was found. Palmitoleate positively correlated with TC, HDL cholesterol, TG and LDL cholesterol levels.
Keywords: Humans; adipozita; Czech Republic; mastné kyseliny; Fatty Acids; mužské pohlaví; Cholesterol, HDL; Česká republika; metabolom; Metabolome; Adolescent; Triglycerides; ženské pohlaví; triglyceridy; LDL-cholesterol; lidé; mladiství; HDL-cholesterol; Adiposity; Male; Cholesterol, LDL; Female